Developing an Innovative Game-Based Learning Model in Physical Education to Improve Literacy and Numeracy Skills of 1st Grade Students - Nengah Kadek Nirma Arya Febyanti; Hari Yuliarto (Gladi : Jurnal Ilmu Keolahragaan, 2025)
Literacy and numeracy have been regarded as a fundamental skill for students’ further learning. Many challenges are still faced by elementary teachers related to the limited sources in improving students’ literacy and numeracy. The current study aimed at developing an innovative game-based learning model in Physical Education (PE) classrooms to improve students’ literacy and numeracy skills. Research and Development (R&) approach was employed by adapting ADDIE model. There were five stages of development; analysis, design, development, implementation, and evaluation. There were 30 of 1st grade students and two PE teachers at Bukit Sunrise School Jimbaran, Bali, selected as research subjects by using total sampling technique. The data were obtained through observation, interview, and test. The observation sheet, interview guide, and test were the research instruments in which the obtained data were analysed quantitatively and qualitatively. The results indicated that the innovative-game learning model had a very high quality and effectively improved students’ literacy and numeracy. These results imply that game-based learning model within PE is an effective alternative to increase students’ fundamental skills.